2003
DOI: 10.14214/sf.498
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage and asymmetry in the root system of Pinus peuce

Abstract: The relationship between the anchorage mechanics and root architecture of Pinus peuce was investigated by carrying out winching tests and examining excavated root systems of 20 mature trees. The root system was dominated by 6.1 ± 1.3 lateral roots, more than 70% of the lateral root cross sectional area (CSA) being distributed in the uppermost 10 cm of soil. Anchorage strength was related to the size of the tree and CSA. The overturning moment of trees was proportional to the diameter at breast height (DBH) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…the rotation axis was below the tree base and the leeward laterals were pushed into the soil. In such soil conditions, Mickovski and Ennos (2003) also reported that asymmetry in the lateral root system did not appear to cause asymmetry in anchorage rigidity, which is consistent with the present results in soil type S1. It was also shown that in soil type S1, the removal of the distal part of the tap root did not change anchorage behaviour of the given root patterns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…the rotation axis was below the tree base and the leeward laterals were pushed into the soil. In such soil conditions, Mickovski and Ennos (2003) also reported that asymmetry in the lateral root system did not appear to cause asymmetry in anchorage rigidity, which is consistent with the present results in soil type S1. It was also shown that in soil type S1, the removal of the distal part of the tap root did not change anchorage behaviour of the given root patterns.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, more assimilates should be invested in roots close to the soil surface if anchorage is to be improved. Such preferential allocation of root biomass at the uppermost soil surface has also been discussed by Mickovski and Ennos (2003) studying Pinus peuce in brown clay soil, and by Danjon et al (2005) with regard to mature maritime pine growing in sandy soil.…”
Section: Discussionmentioning
confidence: 93%
“…In some mangrove species relative root depths differ by both species and growth conditions such as soil compaction, competition for assimilates, water logging, wind force, direction of wave or storm surges, which in turn affects the tree stability (Mickovski and Ennos 2003;Ong et al 2004). To overcome these adverse circumstances, some mangrove species develops above-ground, functional, modified, spreading root systems such as stilt roots/prop roots and buttress roots instead of consistent below-ground tap root system (Ong et al 2004).…”
Section: Specialized Root For Physical Stabilitymentioning
confidence: 99%
“…When these roots spread horizontally, they are able to cover a wider area for collecting nutrients from the soil surface. They spread near the upper soil layer where the main nutrients are available (Crook et al 1997;Mickovski and Ennos 2003;Mendez-Alonzo et al 2015). Buttresses are tension elements, being larger on the side away from the stress of asymmetrical canopies (Young and Perkocha 1994).…”
Section: Specialized Root For Physical Stabilitymentioning
confidence: 99%
“…To predict or develop management techniques to reduce wind damage to forests, it is necessary to be able to model the mechanical behaviour of coarse roots. Most coniferous trees are supported by a system of between 3 and 11 large structural roots (Eis, 1974;Fayle, 1975;Coutts, 1983a;Kuiper & Coutts, 1992;Mickovski & Ennos, 2003), and on shallow rooted trees, these must develop evenly around the tree if it is to remain stable. A tree may be vulnerable to windthrow if it produces very few structural roots, or if large sectors of the root system lack such structural roots (Coutts, 1986;Danjon et al, 2005;.…”
Section: Mechanical Properties Of Rootsmentioning
confidence: 99%